Rantai Nilai Agribisnis Lada Putih di Kecamatan Air Gegas, Kabupaten Bangka Selatan - Pradnya Paramitha, Annisa; Agustina, Fournita; Sitorus, Rostiar (Universitas Medan Area, 2025)
White pepper is seen as an economic pillar by the people of Bangka Belitung Islands Province. Its untapped potential requires attention from stakeholders, therefore, a study of the white pepper agribusiness value chain is needed as a basis for policy making. The purpose of this study is to describe the white pepper agribusiness value chain in South Bangka Regency. This research was conducted in Air Gegas Village, Nyelanding Village, Delas Village, and Air Bara Village from January to August 2025 through a survey. The data used in this study include primary and secondary data collected through observation, interviews, questionnaires, and documentation studies. These data were analyzed using qualitative analysis. The results of this study indicate that the white pepper agribusiness value chain in South Bangka Regency is dominated by the sale of white pepper in the form of grains rather than white pepper in the form of flakes. The parties involved include Agricultural Stores, Farmers, Middlemen, BUMDesMA Mitra Lada Bersatu, Retailers, and Exporters, as well as Consumers, specifically Local Consumers and Global Consumers. The involvement of BUMDesMA Mitra Lada Bersatu provides added value to white pepper despite its limited supply.